2004
DOI: 10.4141/a04-003
|View full text |Cite
|
Sign up to set email alerts
|

Feeding micronized and extruded flaxseed to dairy cows: Effects on digestion and ruminal biohydrogenation of long-chain fatty acids

Abstract: Four lactating Holstein cows fitted with ruminal and duodenal cannulae were used in a 4 × 4 Latin square study to determine the effects of feeding micronized and extruded flaxseed on ruminal biohydrogenation (BH) and digestibility of fatty acids (FA) in the gastrointestinal tract. Four diets were formulated: a control diet with no flaxseed (C); a raw flaxseed diet (RF); a micronized flaxseed diet (MF); and an extruded flaxseed diet (EF). Flaxseed diets contained 126 g kg -1 flaxseed (dry matter basis). Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
12
1
1
Order By: Relevance
“…In the present experiment, digestibilities of oleic, linoleic and linolenic FA were always lower for the RL diet compared to the other diets. In contrast, Gonthier et al [15] observed a lower digestibility of the control diet compared to linseed-supplemented diets, and no difference among linseed-supplemented diets. The digestibility of the control diet may differ according to the basal ration.…”
Section: Intestinal Digestibilitymentioning
confidence: 84%
See 3 more Smart Citations
“…In the present experiment, digestibilities of oleic, linoleic and linolenic FA were always lower for the RL diet compared to the other diets. In contrast, Gonthier et al [15] observed a lower digestibility of the control diet compared to linseed-supplemented diets, and no difference among linseed-supplemented diets. The digestibility of the control diet may differ according to the basal ration.…”
Section: Intestinal Digestibilitymentioning
confidence: 84%
“…The most surprising result of this experiment was the numerically higher amount of linolenic acid at the duodenum with the EL diet than with the RL diet. Other data showed either a lower amount of linolenic acid with extruded linseed [15] or no variation [14]. A part of these differences among trials may be explained by differences in technological processes.…”
Section: Duodenal Flow and Biohydrogenationmentioning
confidence: 94%
See 2 more Smart Citations
“…Since the extrusion process breaks down plant cells, it can be expected that the cytosolic triglycerides would be more accessible to rumen bacteria than when whole seed is fed, because they are more readily available for lipolysis and biohydrogenation (Maddock et al, 2006). Gonthier et al (2004) found that although extrusion increased the disappearance of linolenic acid, it also increased the proportion of intermediate compounds such as trans 18:1 fatty acids in the duodenal flow. The main goal of this study was to examine the effect of increasing levels of extruded cotton seed and canola seed on oleic acid, linoleic acid and linolenic acid concentrations of the plasma, erythrocytes and livers of male Mehraban lambs.…”
Section: Introductionmentioning
confidence: 99%